SPINY LOBSTERS AND THEIR FISHING TECHNIQUES - RAJAN, K. V. MOHAN; MEENAKUMARI, B; BALASUBRAMANYAN, R (Fishery Technology, 2017)
Scores of publications on spiny lobsters and their :fishing techniques are available from various parts of the world. A variety of fishing gears which vary in design and operation are employed for exploiting lobsters. A review of the work carried out on spiny lobsters with special reference to their distribution, fishing gear, fishing methods, baits and crafts in India, Sri Lanka, United States, Australia, South Africa, United Kingdom, Ireland and Portugal based on selected literature are considered and discussed.